Celastrol Alleviates Chronic Obstructive Pulmonary Disease by Inhibiting Cellular Inflammation Induced by Cigarette Smoke via the Ednrb/Kng1 Signaling Pathway - Shi, Ke; Chen, Xi; Xie, Bin; Yang, Sha Sha; Liu, Da; Dai, Gan; Chen, Qiong (Frontiers in Pharmacology, 2018)
Chronic obstructive pulmonary disease (COPD) is a debilitating disease caused by chronic exposure to cigarette smoke (CS). Celastrol is a pentacyclic triterpenoid compound exhibits potent antioxidant and anti-inflammatory activities. Also it is presently known to protect against liver damage induced by type II diabetes. However, its role in COPD is unclear. In this study, we investigated the effects of Celastrol on cellular inflammation in mice exposed to CS and Beas-2B cells treated with CS extract (CSE). C57BL/6 mice and Beas-2B cells were randomly divided into three groups: control group, COPD or CSE group, and Celastrol treatment group. The COPD mice models were subjected to smoke exposure and cell models were treated with CSE. Bioinformatics analysis was performed to identify differentially expressed genes following treatment with Celastrol in COPD, the molecular networks was mapped by Cytoscape. The levels of inflammatory cytokines interleukin-10, monocyte chemoattractant protein-1, and oxidative stress factors superoxide dismutase and catalase were measured by enzyme-linked immunosorbent assay. Hematoxylin and eosin staining to detect the injury of mouse lung tissue. mRNA and protein levels of Ednrb and Kng1 in the tissues and cells were measured by quantitative polymerase chain reaction (PCR) and western blotting, respectively. Apoptosis was measured by flow cytometry and TUNEL staining. Compared to mice in the COPD group, mice treated with Celastrol had significantly reduced levels of inflammatory cytokines interleukin-10 and monocyte chemoattractant protein-1 in the serum and bronchoalveolar lavage fluid, and significantly increased levels of oxidative stress factors superoxide dismutase and catalase. The same results were obtained at the cellular level using Beas-2B cells. Compared to the model groups, Celastrol reduced lung injury in mice and significantly reduced cellular apoptosis. Bioinformatics analysis showed that Ednrb is a target gene of Celastrol and differentially expressed in COPD. Quantitative PCR analysis showed that Ednrb expression in patients with COPD was significantly increased compared to that in healthy controls. Additionally, Celastrol effectively reduced Ednrb/Kng1 expression in both cell and animal models. Celastrol has a therapeutic effect on COPD and may alleviate COPD by inhibiting inflammation development by suppressing the Ednrb/Kng1 signaling pathway.